2001
DOI: 10.1021/tx000266j
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Hepatic 8-Oxo-deoxyguanosine Adducts by 2,3,7,8-Tetrachlorodibenzo-p-dioxin in Sprague−Dawley Rats Is Female-Specific and Estrogen-Dependent

Abstract: 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) is a hepatocarcinogen that induces sex-specific hepatic neoplastic alterations in female, but not male, rats. It has been hypothesized that TCDD-induced alterations in estrogen metabolism lead to increased generation of reactive oxygen species. The resulting oxidative damage to DNA may contribute to TCDD-induced tumor promotion and hepatocarcinogenesis. This hypothesis is supported by previous observations of increased 8-oxo-deoxyguanosine (8-oxo-dG) adduct formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 49 publications
2
35
2
Order By: Relevance
“…3, there was no trend in the numbers of M 1 dG DNA adducts in response to the different doses of TCDD or one of the PHAH mixtures (non-parametric Jonckheere-Terpstra exact test, p > 0.18). This result is consistent with the findings from other investigators who reported no significant changes in the numbers of 8-OHdG adducts after a single exposure to DLC [36,37]. In contrast, subchronic or chronic exposures to the chemicals resulted in an accumulation of 8-OH-dG adducts in animals [36,37].…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…3, there was no trend in the numbers of M 1 dG DNA adducts in response to the different doses of TCDD or one of the PHAH mixtures (non-parametric Jonckheere-Terpstra exact test, p > 0.18). This result is consistent with the findings from other investigators who reported no significant changes in the numbers of 8-OHdG adducts after a single exposure to DLC [36,37]. In contrast, subchronic or chronic exposures to the chemicals resulted in an accumulation of 8-OH-dG adducts in animals [36,37].…”
Section: Resultssupporting
confidence: 92%
“…Additionally, it has been proposed that DNA repair proteins can be impaired by mutations caused by the slow accumulation of DNA adducts over a long period of time [37]. This argument is supported by the findings from previous studies that reported sustained DNA adduct (i.e., 8-OH-dG) accumulation, toxicity, and carcinogenesis [12,36,37,41].…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…In contrast, the environmental pollutant TCDD, which is the most potent AhR agonist, induces CYP1A1 and modulates CYP1B1 expression in MCF-7 cells (Dohr et al, 1995), but is not directly genotoxic. It has been hypothesised that TCDDinduced alterations in estrogen metabolism may lead to increased generation of reactive oxygen species and consequent induction of DNA adducts (Wyde et al, 2001).…”
Section: Discussionmentioning
confidence: 99%